FUNCTIONS OF EUPHEMISM IN PUTU WIJAYA’S SHORT STORY GURU - Jumino Suhadi; M. Manugeren; Purwarno Purwarno; Purwanto Siwi; Susi Ekalestari (University of Kuningan, 2021)
Euphemisms in the form of non-offensive or subtle expressions to replace the one felt to be insulting or unpleasant become guidelines in social interaction, essentially, using words with good meanings or intentions. Euphemism can also be interpreted as an expression that is not straightforward, the driving motive behind the development of pejorative, motivated by a natural human attitude, avoiding conflict by not hurting or offending other people. If there were no euphemisms, there might be depression or demeaning of meaning. This research is focused on the functions of euphemism in the short story entitled Guru written by Putu Wijaya with the concept of the functions of euphemism in speech acts. The research is conducted by descriptive qualitative method related to social phenomena, in this case the uses of euphemism either in a literary or social text. The results show that out of the 15 data obtained, there are 12 data referred to the function of euphemism as a means of speech refinement (80%), 2 as a means of diplomacy (13%, and 1 keeping something secret (6%).